PERCEPTION OF CRIMINALS: WHAT STEREOTYPES HOLD FUTURE LAW ENFORCEMENT OFFICERS? - Ruibyte, Laima; Viduoliene, Evelina; Balseviciene, Birute (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The main reasons for why stereotypes of police officers about criminals are dangerous and affecting the legal system are: firstly, having stereotypes and misconceptions about typical criminals is damaging witness's ability to correctly identify and/or remember the offender’s features; secondly, stereotypes determine the peculiarities of interrogations; thirdly having stereotypes hinders the identification of individuals who actually commit crimes. 270 university students of Law and Police Activity program participated in the study and gave their opinion on the portrait and likely activities of a potential perpetrator. The Criminal Stereotype Questionnaire-Revised (Sparks & MacLin, 2011) was used to evaluate students’ judgment concerning the potential perpetrator’s socially desirable/undesirable personality traits, early years of family life history and childhood and adolescence activities. The results of this study revealed that future law and public security officers refer to delinquent activities during childhood and adolescence as well to adverse parental family life circumstances when predicting criminal behavior rather than personality traits. Furthermore, they have some preconceptions about gender, race and criminal behavior in advance.